Program Kreativitas Mahasiswa (PKM) dalam Meningkatkan Kesehatan Mental Remaja melalui Psikoedukasi Emosi di Kalangan Siswa Sekolah Menengah Atas - Ita Suryaningsih; Syaharani, Umma; Asmirah; Nuranisa; Mutmainna H.; Musdalifa; Chaerunnisa (LESTARI: Jurnal Pengabdian Kepada Masyarakat, 2025)
Based on initial observations and informal interviews with the school counselor and several students at SMAN 3 Maros, issues related to mood swings, peer pressure, and low emotional literacy were identified, which contributed to social conflict and decreased learning focus. In response to these needs, this Community Service Program (PKM) aimed to improve students’ emotional literacy through the psychoeducational seminar “Mood Swings & Friendship Things.” The activity was conducted onsite on November 7, 2025, with 20 student participants, using interactive material delivery and a question-and-answer session. Evaluation results indicated an increase in students’ understanding of emotional concepts, causes of mood swings, and strategies for managing peer conflict. Students also demonstrated improved ability to recognize their emotional states using the emotion-zone framework. This program positively impacted students’ emotional awareness and provided implications for the school to develop more sustainable emotional support services.